Development and validation of a confined space rescue training prototype based on an immersive virtual reality serious game. (January 2022) - Lu, Song; Wang, Fei; Li, Xin; Shen, Qichuan
Abstract: Due to the inherently hazardous nature of the confined space environment and a lack of effective rescue training on on-site personnel attempting the rescue of fellow workers in a confined space, accidents or even multiple fatalities may happen. For this reason, improving the skill set of rescuers is of vital importance. Immersive virtual reality serious games (IVR SG) have been shown to be effective and are now widely used in safety training. However, there is little research on its application in confined space rescue training. To bridge this gap, we have developed a confined space rescue training system (called Rescue Success) based on IVR SG, and then tested its effectiveness in a real environment. We carried out a single-blind, randomized comparative experiment to study and compare the learning effectiveness of using IVR SG compared to an E-lecture in terms of behavioral skills, knowledge acquisition, self-efficacy, and simulation-induced sickness. Our results show that both training methods significantly improve the participant's rescue behavioral skills, knowledge, and self-efficacy. Overall, IVR SG performed better than an E-lecture in all aspects except simulation-induced sickness, where there is no difference between the two methods.